The effect of GnRH Agonist use in Frozen Cycles on pregnancy results (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effect of GnRH agonist use on pregnancy and abortion in the preparation of the endometrium in autologous frozen embryo transfers performed with hormone replacement therapy.Material and Methods: All autologous artificial Frozen – thawed embryo transfer (FET) between 1/2016 and 1/2018 were evaluated retrospectively in order to investigate the effect of GnRH agonist use on pregnancy and abortion rates in frozen embryo FET cycles.Results: 226 patients were included in the study. The mean age of the patients included in the study was 30.76 ± 4.72 years. Of the patients, 144 (63.7%) were diagnosed with unexplained infertility, 20 (8.8) with low ovarian reserve, and 62 (27.4) with male factor. No significant difference was found in terms of pregnancy result and abortion in patients using (N: 22) and not using GnRH agonist (p = 0.212, 1,000).Conclusion: No significant effect of GnRH agonist use on pregnancy rate or abortion was detected in autologous frozen embryo transfers performed with HRT. The prospective studies involving larger patient populations are needed to clarify this subject..
Keywords: GnRH agonist; frozen embryo transfer; pregnancy rate